Exploring peer navigation and support in the quality of HIV care experiences of female sex workers in the Dominican Republic - Tahilin Sanchez Karver; Clare Barrington; Yeycy Donastorg; Martha Perez; Hoisex Gomez; Kathleen R. Page; David Celentano; Katherine Clegg Smith; Deanna Kerrigan (BMC, 2022)
Abstract Background Despite evidence on peer navigation's association with positive HIV outcomes, such as engagement in HIV care and antiretroviral therapy (ART) initiation, the mechanisms through which peer navigation may influence these outcomes have been less explored. The purpose of this study is to describe the role of peer navigation and support on enhancing the quality of HIV treatment and care services experienced by female sex workers (FSWs). Methods Survey data was derived from a quantitative cohort (n = 211) of FSWs living with HIV in the Dominican Republic and complemented with data from two rounds of in-depth interviews (IDIs) from a qualitative subsample (n = 20 per round). Descriptive statistics and multivariable logistic regressions were used to explore the association between peer navigation and relational aspects of care and overall satisfaction of the quality of HIV treatment and care. Thematic analysis was employed to code and synthesize textual data from IDIs. Results 41.2% of the participants reported having had contact with a peer navigator in the last 6 months. Qualitative data revealed that peer navigation and support was instrumental in assisting FSWs linkage to HIV care after diagnosis, elevating FSWs' ability to access more comprehensive clinical care facilities, and promoting agency by improving FSWs' skills to more strategically and effectively engage with the clinic environment and health care providers. Peer navigation was positively associated with experiencing more respectful treatment by clinic staff (AOR: 6.65, 95% CI: 2.32-19.02), and greater satisfaction with overall HIV care services (AOR: 2.57, 95% CI: 1.77-3.74). Conclusion Promoting the full integration of peer navigation into healthcare structures is a strategic approach to enhance the quality of HIV care experienced by FSWs and improve their HIV-related outcomes.